Anomie, Ketidakberdayaan Ekonomi-Sosial-Politik Dalam Tinjauan Tindakan Sosial Max Weber - Sabarudin, Didin (JURNAL KEBANGSAAN RI, 2025)
Intentionally ending one's life by suicide is often an inevitable occurrence in society. Social phenomena in society greatly influence a person's suicide, as happened to mother EN, who reflects behavior experiencing anomie, moral confusion, and a loss of social direction related to dramatic socioeconomic upheaval. Economic-socio-political powerlessness triggered the suicide due to disappointment with her husband, who was considered to be a constant liar and was in endless debt, thus making her feel exhausted from facing the stressful socioeconomic situation and taking shortcuts. Her personal actions are causal to social actions against her two children, her husband, and part of the collectivity of society influenced by social relations that have been based on tradition as a norm of shared life, then changing rapidly due to various influencing factors. This new condition exceeds EN's capabilities, causing her to become frustrated without a normative solution as a binding force. Collective awareness that prioritizes togetherness amidst diversity needs to be created and maintained due to the fading social relations, identity conflicts, social inequality, and changing values ​​that threaten social solidarity. That is the purpose of this paper using a sociological approach with a qualitative explanatory method to understand the reality faced by EN as an individual and social being. Threats to social solidarity and social cohesion are challenges that must be faced together in managing diversity and individual differences that have moral values/norms within the bonds of solidarity and social action that are inclusive, just, and interdependent, while simultaneously maintaining and building a strong community unity as a representation of socio-political change in preventing the tragedy of the loss of our own human civilization.